Proposal of an educational video game for the teaching-learning of the requirements classification in software engineering [Propuesta de un videojuego educativo para la enseñanza-aprendizaje de la clasificación de requisitos en ingeniería de software] (2019)
One of the most relevant phases in software development process is the analysis phase, in which the scope of the software to be constructed is defined through the specification of functional and non-functional requirements. This phase is crucial since a poor specification of the system requirements can generate an extra effort in subsequent phases. At the academic level, shortcomings have been identified in the students of the software engineering courses, in terms of the definition and classification of these requirements, which may affect the quality of the software products of these future professionals. This paper proposes a videogame as a tool to reinforce students skills in these courses, in terms of identification and classification of requirements. The video game was conceived using the Design Thinking methodology, implemented through the GDevelop platform and evaluated from the usability perspective, using Pinelle video game heuristics. © 2019, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.